The Cleveland Clinic Manual of Dynamic Endocrine Testing - Ergin, Ahmet Bahadir; Kennedy, A. Laurence; Gupta, Manjula K.; Hamrahian, Amir H. (Springer International Publishing : Imprint: Springer, 2015)
Developed via a peer review process that included 25 experienced endocrinologists and utilizing the best current evidence, The Cleveland Clinic has created a practical set of protocols for over 25 commonly used dynamic endocrine tests. The cornerstone of clinical endocrinology, these evidence-based protocols play an important role in clinical decision-making and are important element of billing and compliance with high quality standards. Included here are various tests for pituitary and adrenal disorders, thyroid disorders, and glucose metabolism and pancreatic disorders, presented systematically with indications, preparation, materials needed, precautions, procedure, interpretation, and caveats. Filling the gap left by a lack of national guidelines, The Cleveland Clinic Manual of Dynamic Endocrine Testing is an up-to-date practical guide for endocrinologists, nurses, and their staff, inside or outside of the US, who need to perform and interpret dynamic endocrine testing in their everyday practice, as well as medical students, residents and fellows who have interest in endocrinology.